Morinda citrifolia (Noni): A comprehensive review on its industrial uses, pharmacological activities, and clinical trials - Abou Assi, Reem; Darwis, Yusrida; M. Abdulbaqi, Ibrahim; A. khan, Arshad; Lim, Vuanghao; Laghari, M.H. (Elsevier, 2017)
Traditional medical practitioners in Hawaii and Polynesia have used Morinda citrifolia L. (Noni) for centuries to cure or prevent varieties of illnesses. The popularity of M. citrifolia as a dietary supplement, a food functional ingredient, or as a natural health enhancer is increasing throughout the world. M. citrifolia contains phytochemicals that own antibacterial, antiviral, antifungal, antitumor, anthelminthic, analgesic, hypotensive, anti-inflammatory and immune enhancing effects. Moreover, the increasing vogue of M. citrifolia has attracted industries to employ it as a part of various products and for wide applications such as a natural source of medicines and chemical reagents as well as a green insecticidal. The wide spread of M. citrifolia in tropical climate of the globe, from USA to Brazil reaching to Tahiti, Malaysia and Australia, contributed in enriching its uses and potentials due to the variation in harvest locations. M. citrifolia parts including fruits, seeds, barks, leaves, and flowers are utilized on their own for individual nutritional and therapeutical values, however, the fruit is considered to contain the most valuable chemical compounds. This review discusses in details the industrial uses and the pharmacological activities of M. citrifolia fruit, seed, leaf and root, along with their isolated phytochemical compounds, through describing the conducted in vitro and in vivo studies as well as clinical data.